BIMBINGAN DAN PROSES PENGOLAHAN LIMBAH PLASTIK SEBAGAI ALTERNATIF WIRAUSAHA PETUGAS PEMUNGUT SAMPAH - Widjanarko Widjanarko; Agus Hardjito (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Waste matter plastic (especially former drinking water packaging) and community economic level of relatively low on will be essentially had an impact on their the national and state life, because besides feared plastic garbage is to be pollute environment , will appear negative things due to the economic situation of economic low as, theft, robbery, forgery, of child trafficking, malnutrition, and others. Activities devotion to the community (PKM) this purpose of giving guidance and processing plastic waste by means of enumerated, in relation to the addition of value plastic waste packaging mineral water to improve living standard Officers Garbage Collector (PPS) in Kelurahan Tunjungsekar, Kecamatan Lowokwaru, Kota Malang. In implementation of activities PKM this methods used is conducting observations and assistance to the social protection programs, prepared matter, preparation instrument , material, and a required in processing plastic waste that includes: (1) Way election waste plastic to be processed, (2) Election processing , (3) The determination of the type machine used for processing plastic waste. The evaluation will be done to see processing plastic waste run the social protection programs for each the outcome of the activities start first to produce plastic processed. At the end of the implementation of the done placement plastic waste crusher machine scale home in the house of PPS.